PEMIMPIN IDEAL DALAM PERSPEKTIF HADIS - Anisatun Muthi’ah (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2017)
The ideal leader in Islamic advice should be included in the sense of a helper, for the leader is in charge of protecting the people he leads and trying to help and rescue them when hardships and disasters strike, for the leader is responsible for everything that is and what is happening in his territory and about the people he leads. A chosen leader is to lead members of his group to be able to realize common goals.